The Correlation between Dysmenorrheal Pain with Flatus - Lidia Widia; Desi Kumala; Rena Oki Alestari; Ivana Devitasari; Evy Kasanova (Budapest International Research and Critics University, 2023)
Dysmenorrheal is a genetic complaint due to an imbalance of the hormone progesterone in the blood causing the most common pain occurring in women. Women with dysmenorrheal produce prostaglandin in 10 times more than women who are not dysmenorrheal. Prostaglandin causes increased uterine contractions, and excessive levels will activate the large intestine and cause flatus. This condition causes uncomfortable so that daily activities become disturbed. Based on the results of interviews 15 students experienced a sense flatus and defecate at the time of dysmenorrheal pain. This study aims to determine the correlation between dysmenorrheal pain with the occurrence of flatus and defecation. The design of this study by using cross sectional. The sample in this study was 58 students with total sampling technique. The result of this study was chi square test on dysmenorrheal pain with flatus obtained p value <0,05 (0,002) it means that there was correlation between dysmenorrheal pain with flatus.The conclusion of this study that there was a correlation between dysmenorrheal pain with flatus.